PLURALISME INFORMASI: SEBUAH JALAN UNTUK MENEGUHKAN PLURALISME MASYARAKAT (Sebuah Studi Tentang Implementasi Undang-undang No. 40 Tahun 1999) = INFORMATION PLURALISM : A WAY TO STRENGTHEN THE COMMUNITY PLURALISM ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The study examines the implementation of the Act No. 40 of 1999. Under the regulation, the Indonesian press: (i) is no longer a component of the state